2003
DOI: 10.1021/ac0262210
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Blood Immunoassay Using Gold Nanoshells

Abstract: A rapid immunoassay capable of detecting analyte within complex biological media without any sample preparation is described. This was accomplished using gold nanoshells, layered dielectric-metal nanoparticles whose optical resonance is a function of the relative size of its constituent layers. Aggregation of antibody/nanoshell conjugates with extinction spectra in the near-infrared was monitored spectroscopically in the presence of analyte. Successful detection of immunoglobulins was achieved in saline, serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
446
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 653 publications
(455 citation statements)
references
References 25 publications
2
446
0
7
Order By: Relevance
“…An early demonstration of photothermal therapy was reported by Halas et al [160]. Using nanoshells with a 110 nm silica core diameter and a 10 nm Au shell, the authors reported significant reduction of human breast carcinoma epithelial cells (SK-Br-3) both in vitro and in a mouse model.…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…An early demonstration of photothermal therapy was reported by Halas et al [160]. Using nanoshells with a 110 nm silica core diameter and a 10 nm Au shell, the authors reported significant reduction of human breast carcinoma epithelial cells (SK-Br-3) both in vitro and in a mouse model.…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%
“…Another parameter involved in heat generation is the power of the operating laser as well as whether the laser is run in continuous wave (CW) or pulsed wave (PW) mode when interacting with nanoparticles [150,[159][160][161][162][163]. While there is still some debate as to which mode is best, pulsed mode is generally considered more efficient than continuous mode for heating nanoparticles in photothermal applications [150,[164][165][166][167][168].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%
See 2 more Smart Citations
“…From a practical perspective, the tunable optical properties of nanostructures make it possible to use these materials in surfaceenhanced spectroscopy, [10][11][12][13][14] optical filters, 15,16 plasmonic devices, [17][18][19][20] and sensors. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Until recently, there were only limited methods for the synthesis of monodisperse, nonspherical noble metal nanoparticles, which meant that the practical applications of these particles were limited. Recent advances in controlled syntheses of spheres, 36,37 rods, [38][39][40] triangular prisms, [41][42][43] disks, [44][45][46] cubes, 47 and branched nanocrystals 48 have improved both the fundamental understanding and practical use of these nanoparticles for sensing and spectroscopic devices.…”
Section: Introductionmentioning
confidence: 99%